Accessible instructional design - Edyburn, Dave L. (Bingley, U.K. : Emerald, 2015)
The Advances in special education technology series is designed to focus international attention on applications of technology for individuals with disabilities. Outstanding researchers from around the world will contribute chapters synthesizing the research evidence on specific types of technology applications that improve access, engagement, and learning outcomes of diverse learners.The scope of contributions will cover subfields known as assistive technology, instructional design, instructional technology, online learning, personalized learning, and universal design for learning and will encompass both formal and informal learning settings across the lifespan. Instructional designers often fail to consider issues of accessibility when creating educational materials. As a result, students with disabilities frequently encounter physical, sensory, or cognitive barriers that prevent them from accessing, engaging, and succeeding in learning activities. This volume will examine issues of accessibility and how designers can improve the quality of educational materials by embedding supports that anticipate the special learning needs of diverse learners.
Accessible instructional design : designing for differences / Dave L. Edyburn -- What do you need to create and maintain web accessibility? / Cyndi Rowland, Jonathan Whiting, Jared Smith -- Universal design for online learning / Anne Guptill -- Accommodation, access, large scale assessment : possibilities for universal design / Evelyn Hickey -- Refocusing instructional design / Randall Boone, Kyle Higgins -- Design for more types : designing text to support the access, engagement, and success of diverse learners / Dave L. Edyburn, Keith D. Edyburn.
Includes index.
Print version record
Keywords: Education -- Special Education -- General; Teaching of physically disabled students; Barrier-free design; Architecture -- Human factors; Architecture and society